POLÍTICA DE INTERIORIZAÇÃO DO ENSINO SUPERIOR: TAXA DE SUCESSO NA GRADUAÇÃO NA UNIVERSIDADE FEDERAL DO PARANÁ - Ricardo Leitoles Corrêa (Universidade Federal de Santa Catarina, 2018)
With the aim of democratizing higher education in Brazil, several public policies have been implemented. Among them is the expansion of public higher education into inland (not main cities) areas -- a process known in Portuguese as "interiorization" (interiorização) -- mainly driven by the Restructuring and Expansion Program of Federal Universities - REUNI. The purpose of the program was to expand access to and stay in higher education. The objective of this paper is to evaluate the effectiveness of the interiorization of higher education in the scope of the Federal University of Paraná after 2007 by means of the graduation success rate in university satellites located outside the state capital. This aim was established in order to be able to evaluate the REUNI program, and is also found in the National Education Plan. The study is of a descriptive research design, adopting a quantitative approach and using indicators for data analysis. It can be asserted that the interiorization process of the Federal University of Paraná contributed to the reduction of the overall success rate of undergraduate courses, distancing itself from the expected goal. The three satellite campuses analyzed presented values below the mean of the UFPR main (Curitiba) campuses after 2010.